2016
DOI: 10.18069/fusbed.54896
|View full text |Cite
|
Sign up to set email alerts
|

Li̇se 12. Sinif Öğrenci̇leri̇ni̇n İngi̇li̇zce Öz Yeterli̇k İnançlarina İli̇şki̇n Görüşleri̇

Abstract: ÖZETBu çalışmanın amacı lise 12. sınıf öğrencilerinin İngilizce öz yeterlik inançlarının ne düzeyde olduğunu belirlemektir. Bu amaç doğrultusunda araştırmada Yanar ve Bümen (2012) ABSTRACTThe aim of this study is to determine high school 12 th grade students' beliefs of self-efficacy in English. For that aim, self-efficacy scale for English developed by Yanar and Bümen (2012) was used in the study. The scale included four sub-scales named reading, writing, listening and speaking. Cronbach's alpha for the read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
0
2
0
7
Order By: Relevance
“…On the other hand, some studies have found opposite results. For example, Gömleksiz & Kılınç (2014) determined that the English self-efficacy beliefs of male 12th-grade high school students were higher than that of female students. Similar results were found by Mengi (2011), who studied secondary school students.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…On the other hand, some studies have found opposite results. For example, Gömleksiz & Kılınç (2014) determined that the English self-efficacy beliefs of male 12th-grade high school students were higher than that of female students. Similar results were found by Mengi (2011), who studied secondary school students.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…İngilizce öğrenmek için yüksek düzeyde azim ve kararlılığa sahip değildirler. Literatürdeki bazı araştırmalar da bu sonuçla paralellik göstermektedir (Şener ve Erol, 2017;Kaya, 2016;Karanfil, 2015;Oğuz ve Akkaş Baysal, 2015;Gömleksiz, 2014). Öğrencilerin İngilizce özyeterlik inançları okuma, yazma, dinleme ve konuşma becerileri açısından karşılaştırıldığında ise öğrenciler bu becerilerin tümünde yine orta düzeyde özyeterlik inancına sahip olmakla birlikte, en yüksek okuma becerisinde kendilerine inanmaktadırlar.…”
Section: Sonuç Ve Tartişmaunclassified
“…İngilizce öğretiminde okuma, yazma, dinleme ve konuşma olmak üzere dört temel beceri bulunmaktadır. Büyükduman'a (2006) (White ve Bowers, 2008;Raoofi, Tan ve Chan, 2012;Siritararatn, 2013;Gömleksiz ve Kılınç, 2014;Güç, 2019).…”
Section: Introductionunclassified
“…Alanyazın incelendiğinde öz yeterlik inancı ile ilgili birçok çalışmanın (Alcı ve Yüksel, 2012;Anyadubalu, 2010;Aykol, 2017;Ghonsooly ve Elahi, 2010;Gömleksiz ve Kılınç, 2014;Hancı Yanar, 2008;Hsieh, 2008;Kanadlı ve Bağçeci, 2015;Karanfil ve Arı, 2016;Mills, Pajares ve Herron, 2006;Ocak ve Akkaş Baysal, 2016;Todaka, 2017) yapıldığı görülmektedir. Bu çalışmalar incelendiğinde İngilizceye yönelik öz yeterlik inancı ile ilgili çalışmaların daha kısıtlı olduğu görülmektedir.…”
Section: Introductionunclassified